Techno-economical optimization using Box-Behnken (BB) design for chemical oxygen demand and chloride reduction from hospital wastewater by electro-coagulation - Bajpai, Mukul (Water environment research : a research publication of the Water Environment Federation, 2020)
© 2020 Water Environment Federation.